2023
DOI: 10.3390/ijms24076117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Seed Dormancy Using Re-Sequenced Germplasm under Multiple Conditions in Rice

Abstract: Seed dormancy is a key factor used to determine seed germination in rice production. So far, only a few genes controlling seed dormancy have been reported, and the genetic mechanism of rice seed dormancy is still elusive. In this study, a population of 195 diverse re-sequenced accessions from 40 countries was evaluated for the seed germination rate (GR) without dormancy breaking (WDB) as a control and under dry heating (DH) and gibberellic acid (GA) treatments, as dormancy breaking agents to identify QTLs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…enzyme-encoding genes, OsGST3 was specifically shown to respond to various stress hormones (Chen et al, 2023), and OsPDIL1-1 overexpression in transgenic rice was shown to enhance abiotic stress tolerance (Xia et al, 2018), possibly by controlling the production of ROS (Zhao et al, 2023). It was also shown that the aminomethyltransferase gene LOC_Os06g04380 was differentially expressed after arsenic treatment (Norton et al, 2008), that peptidyl-prolyl cis/trans isomerase genes have various functions in response to environmental stresses (Ahn et al, 2010), and that LTPL130 was previously selected as a candidate gene located on chr.…”
Section: Cold Tolerance Trait Mappingmentioning
confidence: 99%
“…enzyme-encoding genes, OsGST3 was specifically shown to respond to various stress hormones (Chen et al, 2023), and OsPDIL1-1 overexpression in transgenic rice was shown to enhance abiotic stress tolerance (Xia et al, 2018), possibly by controlling the production of ROS (Zhao et al, 2023). It was also shown that the aminomethyltransferase gene LOC_Os06g04380 was differentially expressed after arsenic treatment (Norton et al, 2008), that peptidyl-prolyl cis/trans isomerase genes have various functions in response to environmental stresses (Ahn et al, 2010), and that LTPL130 was previously selected as a candidate gene located on chr.…”
Section: Cold Tolerance Trait Mappingmentioning
confidence: 99%